(3EbJUGO hJSjjQ GdeDSSI (B/s - (3Hf MHjH, YHO GdQRGbs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2000)
(3Gdeaghe GdfXGej ddeDSSI(B- (3fXGe GdeDSSI(B- (3fXGe GdJSjjQ GdESJQGJjLj ddeDSSI(B.s
Keywords: (3EbJUGO GdeDSSIs; (3JSjjQ GdeDSSIs